2001
DOI: 10.37570/bgsd-2001-48-06
|View full text |Cite
|
Sign up to set email alerts
|

Late Pliocene Greenland – The Kap København Formation in North Greenland

Abstract: The Kap København Formation, North Greenland, is a 100-m thick succession of predominantly shallow marine nearshore sediments, dated to c. 2.4 ma. The abundant well preserved remains of mosses, land plants, foraminifers, ostracodes, insects, cladocers, molluscs, and a few vertebrates enable a detailed reconstruction of terrestrial and marine environments and climate. The sediments indicate a complex sea-level history implying combined glacioisostatic and -eustatic control. This is supported by the faunal and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 2 publications
3
38
0
Order By: Relevance
“…Low nuclide concentrations, yet high a 26 Al i / 10 Be i ratio, are consistent with erosion of several meters of surface material prior to 2.0 Ma (which would have higher 10 Be i and 26 Al i concentrations and a lower 26 Al i / 10 Be i ) followed by brief exposure at depth, then erosion and subglacial transport to the shelf margin. Such early glacial erosion followed by exposure fits with ice‐free conditions indicated by the ~2 Ma Kap København Formation that putatively predates the diamict we analyzed (Funder et al, ). The presence of 26 Al i supports the age model (Knutz et al, ); if the diamict was much older than 2.0 Ma, 26 Al i would not be preserved due to its 7 × 10 5 year half‐life.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Low nuclide concentrations, yet high a 26 Al i / 10 Be i ratio, are consistent with erosion of several meters of surface material prior to 2.0 Ma (which would have higher 10 Be i and 26 Al i concentrations and a lower 26 Al i / 10 Be i ) followed by brief exposure at depth, then erosion and subglacial transport to the shelf margin. Such early glacial erosion followed by exposure fits with ice‐free conditions indicated by the ~2 Ma Kap København Formation that putatively predates the diamict we analyzed (Funder et al, ). The presence of 26 Al i supports the age model (Knutz et al, ); if the diamict was much older than 2.0 Ma, 26 Al i would not be preserved due to its 7 × 10 5 year half‐life.…”
Section: Discussionsupporting
confidence: 63%
“…Understanding Greenland Ice Sheet (GrIS) behavior during warmer‐than‐present climates is critical (Clark et al, ); yet, the behavior and state of the GrIS before the Last Glacial Maximum remain poorly understood (Bierman et al, ) because present ice cover obscures and glacial erosion removed terrestrial records of GrIS history (Funder et al, ; McFarlin et al, ). Much of the known GrIS deep time history relies on marine archives including seismic surveys (Knutz et al, ) and sediment cores from deep ocean drilling (Bierman et al, ; Helland & Holmes, ; Reyes et al, ; Tripati et al, ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by either reducing ablation (lowering air temperatures) or enhancing accumulation (precipitation) or some combination of both. Compared with the Late Pleistocene, air temperatures in the Early Pleistocene appear higher (36)(37)(38)(39), while precipitation estimates are, at best, tentative (38,39). Assuming that air temperatures were warmer, enhanced precipitation (accumulation) would be required to sustain low-slung ice sheets in the Early Pleistocene, which, given the increased enthalpy, is not unrealistic.…”
Section: Discussionmentioning
confidence: 99%
“…The origin and transformation of locally derived, impact-affected organic carbon from the crater was investigated by Garde et al (2020), who showed that it was derived from coniferous trees such as Pinus or Picea. Forests of coniferous trees cannot grow anywhere in Greenland today, but they existed up to ∼80°N in warm periods between 3.0 Ma and 2.4 Ma (Fyles et al, 1991;Funder et al, 2001).…”
Section: Introductionmentioning
confidence: 99%